Materiales para una diacronía de las versiones de los evangelios andalusíes = Materials for a diachrony of the versions of the Andalusian gospels - Monferrer-Sala, Juan Pedro (Cauriensia, 2024)
In the present article we analyze a text (Mk 7,24-30.31-37) contained in the archaic version of the Andalusi gospels with the aim of studying the several revisions done by bilingual Latin-Arabic translators/revisers. Thereby, we will be able to determine how and how many were the several revision processes experienced by the various versions of the gospels that circulated in al-Andalus during the 9th to 12th centuries, and later in the north of the peninsula and North Africa. The study includes an análisis of the techniques and strategies used by the translators/revisers, a very important tool that helps us to know how the various revision processes that the Andalusi versions of the gospels underwent over several centuries.